2020
DOI: 10.14739/2310-1237.2020.2.212727
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the cardiac cholinergic response to adrenalin-induced myocardial necrosis and light desynchronosis

Abstract: The aim was to identify sex differences in the cardiac response to cholinergic stimuli in the development of myocardial necrosis and light desynchronosis. Materials and methods. Experiments were conducted in 144 albino rats (72 males, 72 females). Myocardial necrosis was induced by adrenaline (0.5 mg/kg, intramuscularly). The intensity of bradycardia that occurred as a response to intravenous acetylcholine injection and electrical stimulation of vagus nerve was measured. The animals were divided into 4 groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Given the negative impact of diabetes on the myocardium, especially during pregnancy, it is worth noting that light disturbance also has a negative impact on myocardial metabolism and functional activity. In a rat experiment, it was shown that dark deprivation significantly enhances the pathogenic effect of epinephrine on the myocardium of animals, as evidenced by an increase in the area of cardiomyocyte damage in the model of epinephrine necrosis, high free radical oxidation activity, and a deficiency of antioxidant protection [66], while simultaneously reducing the vagal control of cardiac activity [67].…”
Section: Aimmentioning
confidence: 99%
“…Given the negative impact of diabetes on the myocardium, especially during pregnancy, it is worth noting that light disturbance also has a negative impact on myocardial metabolism and functional activity. In a rat experiment, it was shown that dark deprivation significantly enhances the pathogenic effect of epinephrine on the myocardium of animals, as evidenced by an increase in the area of cardiomyocyte damage in the model of epinephrine necrosis, high free radical oxidation activity, and a deficiency of antioxidant protection [66], while simultaneously reducing the vagal control of cardiac activity [67].…”
Section: Aimmentioning
confidence: 99%